Vulnerability, social value and the equitable sharing of benefits from research: beyond the placebo and access debates - Kurihara, Chieko; Greco, Dirceu; Dhai, Ames; Matsuyama, Kotone; Baroutsou, Varvara (Frontiers in Medicine, 2024)
The vulnerability of research participants is a critical topic for the 2024 revision of the Declaration of Helsinki, with the proposal to include “social value. ” However, this proposal has been withdrawn and the relationship between the two concepts has not been clarified. This paper attempts to clarify: (1) the recent reform for the ethical inclusion of vulnerable study participants to promote diversity; (2) the social value, prerequisite for everyone, especially for those who are vulnerable and the most in need; (3) the requirements for promoting the inclusion of vulnerable participants, in particular the review of the norms for placebo-controlled trials and post-trial access; (4) finally, the direction of research ethics reform to achieve social value and equitable global health.